Targeting the Family : A Discourse Analysis of Dancow's 2024 Marketing Strategies - Ma, Cynthia; Delfi Nazilah Lubis; Theofani Leonita Siagian; Nikita Tantira; Lydia Permata Sari; T. Thyrhaya Zein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
Advertisements play a significant role in shaping how we perceive products and make decisions. This study explores how two Dancow advertisements—Dancow 1+ Imunutri and Dancow Fortigro Coklat—use language and visuals to connect with their audiences. Using Fairclough’s Critical Discourse Analysis (CDA) framework, the data, which includes transcribed dialogues and visuals, were taken from the SOOYA CHAN YouTube channel. The findings reveal that while both ads emphasize key nutrients like DHA and iron, they speak to parents in different ways. The Dancow 1+ Imunutri ad focuses on affordability and nutrition for toddlers, reassuring parents of their role in supporting early growth. Meanwhile, the Dancow Fortigro Coklat ad highlights taste and cognitive benefits for school-aged children, connecting with parents’ hopes for their kids’ education and enthusiasm. These findings show how advertisements reflect societal values, especially the central role of mothers in nurturing their children. With only two ads analysed due to time constraints, future studies could look at a broader range of advertisements and explore how audiences respond to them to better understand marketing strategies.